A method for modifying the interface of an all-solid-state polymer electrolyte and its application in secondary ion batteries

CN118017043BActive Publication Date: 2026-11-03SUN YAT SEN UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410149276.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-02-02
Publication Date
2026-11-03
Estimated Expiration
2044-02-02

AI Technical Summary

Technical Problem

The all-solid polymer electrolyte film suffers from problems such as low room temperature ionic conductivity, high electrolyte/electrode interface impedance, and low battery energy density.

Method used

By selecting appropriate solvents for the polymer and electrolyte salt, an electrolyte solution is prepared to soak the all-solid polymer electrolyte membrane. The soaking time is controlled to remove free solvent molecules from the surface, and the interface is modified through the complexation of solvent molecules with the polymer and electrolyte salt.

Benefits of technology

It improves room temperature ionic conductivity, simplifies the operation process, facilitates large-scale production, and is suitable for high-capacity battery assembly with metal anodes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118017043B_ABST
    Figure CN118017043B_ABST
Patent Text Reader

Abstract

The application provides a full-solid-state polymer electrolyte interface modification method and application thereof in secondary ion batteries, and belongs to the technical field of solid-state batteries. According to the types of the polymer and the electrolyte salt in the full-solid-state polymer electrolyte film, a solvent which is good for the polymer and the electrolyte salt is selected, an electrolyte solution is prepared by using the selected solvent, the electrolyte film is soaked in the electrolyte solution, the soaking time is controlled, the soaked electrolyte film is taken out from the electrolyte solution, the free solvent molecules on the surface of the electrolyte film are removed, and the interface-modified full-solid-state polymer electrolyte film is obtained through the complexation between the solvent molecules and the polymer and the electrolyte salt. A small amount of complexed solvent molecules can improve the movement ability of the polymer molecular chain, and is beneficial to the diffusion of the dissociated secondary metal ions, so that the polymer electrolyte film with high room-temperature ionic conductivity is obtained. The method is simple in technical operation, reliable, and convenient for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solid-state battery technology, specifically relating to an all-solid-state polymer electrolyte interface modification method and its application in secondary ion batteries. Background Technology

[0002] All-solid-state batteries use solid electrolytes to replace the electrolytes and separators of traditional secondary ion batteries, resulting in greater safety, higher energy density, and stronger cycle performance. They have become the industry's recognized main research direction for next-generation power batteries. Solid electrolytes are the core component of all-solid-state batteries, possessing the following fundamental characteristics: high ionic conductivity, high ion transport number, good solid-solid interface compatibility, excellent electrochemical stability, and good mechanical properties. Among these, polymer solid electrolytes offer excellent mechanical properties, can be used to fabricate large-capacity cells, are easy to process, and their fabrication process and electrochemical performance are similar to existing commercially available liquid electrolyte-based secondary ion batteries, making them the most readily mass-producible solid-state battery currently recognized.

[0003] Currently reported all-solid-state polymer electrolytes still have significant room for improvement in terms of high room-temperature ionic conductivity, low electrolyte / electrode interfacial resistance, and high energy density. To improve the room-temperature ionic conductivity of all-solid-state polymer electrolytes, the polymer matrix is ​​typically doped or modified to suppress polymer crystallization or lower its glass transition temperature; however, these processes are often complex and have poor reliability. To reduce the interfacial resistance of the electrolyte / electrode materials, researchers often improve interfacial contact by adding liquid electrolyte dropwise between the two interfaces or by applying high pressure to the electrodes; however, these processes also have poor reliability. Meanwhile, some researchers have attempted to prepare solid-state polymer electrolytes through in-situ polymerization, which has initially addressed the problems of low room-temperature ionic conductivity and high electrolyte / electrode interfacial impedance. However, this process still suffers from difficulties in controlling the reaction process, the presence of small molecule residues in the reaction products, and the complexity of the polymerization process. There are relatively few research reports on high energy density. It is often achieved by using a high-pressure resistant polymer matrix or adding inorganic fillers to the polymer matrix to prepare polymer composite solid electrolytes. Compared with other solid electrolyte materials such as sulfides and oxides, polymer solid electrolytes perform poorly in terms of electrochemical stability window and high-pressure resistance. Summary of the Invention

[0004] The purpose of this invention is to address the aforementioned shortcomings of the prior art by providing a method for modifying the interface of an all-solid-state polymer electrolyte and its application in secondary ion batteries, specifically solving the problems of low room-temperature ionic conductivity, high electrolyte / electrode interface impedance, and low battery energy density of all-solid-state polymer electrolyte films.

[0005] To achieve the above objectives, the present invention adopts the following technical solution: The first objective of this invention is to provide a method for modifying the interface of an all-solid polymer electrolyte. Based on the types of polymer and electrolyte salt in the all-solid polymer electrolyte membrane, a solvent with good properties for both the polymer and electrolyte salt is selected. An electrolyte solution is prepared using the selected solvent. The all-solid polymer electrolyte membrane is then immersed in the electrolyte solution for a controlled immersion time. The immersed all-solid polymer electrolyte membrane is then removed from the electrolyte solution, and free solvent molecules on the surface of the membrane are removed. An interface-modified all-solid polymer electrolyte membrane is obtained through the complexation between the solvent molecules and the polymer and electrolyte salt.

[0006] Furthermore, the polymer includes any one of the following: homopolymers of polyethylene oxide (PEO), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), block copolymers (such as polyisoprene-b-polystyrene-b-polyethylene oxide, polystyrene-b-polyethylene oxide, etc.), or graft copolymers (such as polymethyl methacrylate-g-polyisoprene, polyacrylonitrile-g-polybutadiene, etc.).

[0007] Furthermore, the electrolyte salt is any one or more of lithium salt, sodium salt, potassium salt, and zinc salt. The lithium salt includes any one of LiTFSI, LiFSI, LiClO4, LiAsF6, LiPF6, and LiBF4. The potassium salt includes any one of KTFSI, KFSI, KPF6, and KBF4. The sodium salt includes any one of NaTFSI, NaFSI, NaPF6, NaBF4, and NaAsF6. The zinc salt includes any one of ZnTFSI, ZnFSI, ZnPF6, and ZnBF4.

[0008] Furthermore, the solvent includes one or more of tetrahydrofuran, 1,3-dioxapentane, diethyl carbonate, ethylene carbonate, propylene carbonate, acetonitrile, toluene, and acetone.

[0009] Furthermore, the soaking time is 30~300s.

[0010] Furthermore, methods for removing surface free solvent molecules from all-solid polymer electrolyte membranes include any one or a combination of methods such as wiping, vacuum drying, and glove box settling.

[0011] A second objective of this invention is to provide a surface-modified all-solid polymer electrolyte membrane.

[0012] A third objective of this invention is to provide the application of surface-modified all-solid polymer electrolyte membranes in the preparation of secondary ion batteries.

[0013] Furthermore, the secondary ion battery includes any one of lithium secondary batteries, zinc secondary batteries, potassium secondary batteries, and sodium secondary batteries.

[0014] A fourth objective of the present invention is to provide a secondary ion battery having a positive electrode, a negative electrode, and a separator disposed between the positive and negative electrodes, the separator comprising the aforementioned surface-modified all-solid-state polymer electrolyte membrane.

[0015] Compared with the prior art, the beneficial effects of the present invention are: (1) The all-solid polymer electrolyte interface modification method provided by the present invention involves selecting a solvent that is effective for both the polymer and the electrolyte salt in the all-solid polymer electrolyte membrane, based on the types of polymer and electrolyte salt in the membrane. The electrolyte salt is then used to prepare an electrolyte solution with the selected solvent. The all-solid polymer electrolyte membrane is immersed in the electrolyte solution for a controlled immersion time. The immersed membrane is then removed from the electrolyte solution, and the free solvent molecules on the surface of the membrane are removed. The interface-modified all-solid polymer electrolyte membrane is obtained through the complexation between the solvent molecules and the polymer and electrolyte salt, exhibiting high room temperature ionic conductivity (>10). -4 S / cm).

[0016] (2) The all-solid polymer electrolyte interface modification method provided by the present invention is simple to operate and reliable.

[0017] (3) The surface-modified all-solid polymer electrolyte membrane provided by the present invention is compatible with existing secondary battery assembly processes, which facilitates large-scale production.

[0018] (4) The surface-modified all-solid polymer electrolyte membrane provided by the present invention can be matched with metal anodes to assemble high-capacity lithium, zinc and other metal batteries. Attached Figure Description

[0019] Figure 1 A flowchart of the all-solid-state polymer electrolyte interface modification method provided by the present invention; Figure 2 This is a schematic diagram of the mechanism of the all-solid-state polymer electrolyte interface modification of the present invention; Figure 3 A flowchart illustrating the assembly process of a secondary ion battery with a metal anode provided by this invention. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of the present invention clearer, embodiments of the present invention are described in detail below. Examples of these embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0021] refer to Figure 1 The flowchart below illustrates the method for modifying the interface of an all-solid polymer electrolyte provided by this invention. Based on the types of polymer and electrolyte salt in the all-solid polymer electrolyte film, a solvent with good properties for both the polymer and electrolyte salt is selected and prepared to the required concentration with the corresponding electrolyte salt. Then, the all-solid polymer electrolyte film is immersed in the prepared electrolyte solution. The immersion time is controlled, and the immersed polymer electrolyte film is removed from the electrolyte solution. Free solvent molecules on the surface of the electrolyte film are removed by wiping, high-temperature drying in a vacuum oven, and settling in a glove box, resulting in a surface-modified polymer electrolyte film.

[0022] refer to Figure 2 The diagram illustrates the mechanism of the all-solid-state polymer electrolyte interface modification of this invention. The complexation between solvent molecules and the polymer and electrolyte salt facilitates the dissociation of the electrolyte salt, thereby yielding more secondary metal ions that can freely diffuse during charging and discharging. A small amount of complexed solvent molecules can enhance the mobility of polymer molecular chains, which is manifested in inhibiting polymer crystallization or lowering the glass transition temperature of the polymer chains. The enhanced mobility of polymer molecular chains facilitates the diffusion of dissociated secondary metal ions, resulting in polymer electrolyte thin film materials with high room temperature ionic conductivity.

[0023] refer to Figure 3 This is a flowchart illustrating the assembly process of a secondary ion battery with a metal anode provided by the present invention. Because the modified all-solid-state polymer electrolyte film provided by the present invention does not contain free solvent molecules, it can be assembled with metal anodes such as lithium, zinc, sodium, and potassium to form a stable, high-capacity metal battery. Furthermore, due to its good flexibility and processability, the polymer electrolyte film can be used to assemble coin cells or pouch cells using existing commercial secondary lithium-ion battery assembly processes.

[0024] Example 1 Lithium bis(trifluoromethanesulfonyl)amino (LiTFSI) and polyethylene oxide (PEO) were used as the electrolyte salt and polymer matrix material, respectively; tetrahydrofuran (THF) was used as the electrolyte solvent, but other solvents such as 1,3-dioxane (DOL), diethyl carbonate (DEC), ethylene carbonate (EC), propylene carbonate (PC), acetonitrile (ACN), and acetone (DMK) could also be used; lithium iron phosphate was used as the positive electrode material, but lithium cobalt oxide, lithium manganese oxide, and nickel-cobalt-manganese ternary materials could also be used; lithium metal was used as the negative electrode material. PEO and LiTFSI were dissolved in THF at a Li:EO molar ratio of 1:1, and polymer electrolyte films were prepared using solvent casting and template methods. The samples were placed in a vacuum oven at 120°C and evacuated for 48 hours to remove most of the solvent. Then, the samples were transferred to a nitrogen-atmospheric glove box and allowed to stand for 1-2 weeks until the solvent completely evaporated, resulting in a PEO / LiTFSI all-solid-state polymer electrolyte film. A 1 g / mL LiTFSI THF solution was prepared as the electrolyte and placed in a narrow-mouthed bottle with a sealed stopper. In a glove box, the PEO / LiTFSI all-solid polymer electrolyte membrane was immersed in the LiTFSI solution for approximately 0.5 minutes. The immersed electrolyte membrane was carefully removed from the narrow-mouthed bottle, and the solvent on the sample surface was carefully wiped off with lens paper. The sample was then left to stand in a glove box (nitrogen atmosphere) for 1–10 hours to ensure the removal of free THF solvent molecules. The room-temperature ionic conductivity of the obtained electrolyte membrane was measured using electrochemical impedance spectroscopy (Wang et al. Nature Reviews Methods 2021, 1, 41.). The room-temperature ionic conductivity of the obtained sample was 1.1 × 10⁻⁶. -4 The S / cm ratio is significantly higher than that of the PEO / LiTFSI all-solid-state polymer electrolyte film without interface modification, which is ~5.1×10⁻⁶. -6 S / cm. This room-temperature ionic conductivity value is comparable to that of the PEO / LiTFSI gel solid electrolyte obtained by interface modification with N-methylpyrrolidone vapor reported in the literature (Renna et al. 2020 Journal of Electrochemical Society, 2020, 167, 070542.) (4.9 × 10⁻⁶ S / cm). -4(S / cm). The electrolyte membrane was assembled with the previously prepared positive and negative electrodes to form a CR2032 battery for battery performance testing. The battery assembly steps included: in a glove box, placing the lithium iron phosphate positive electrode, solid electrolyte membrane, lithium sheet, stainless steel gasket, and funnel spring into the positive electrode shell of the battery in sequence; then, covering the negative electrode shell and sealing it with a button cell sealing machine to obtain the CR2032 battery. Testing at 60 ℃ showed that the constant current charge-discharge capacity at 0.1C could reach 150 mAh / g, but the battery capacity showed a significant decrease with increasing charge-discharge cycles (>10).

[0025] Example 2 Lithium bis(trifluoromethanesulfonyl)amino (LiTFSI) and polyisoprene-b-polystyrene-b-polyoxyethylene (ISO) block copolymer were used as the electrolyte salt and polymer matrix material, respectively; tetrahydrofuran (THF) was used as the electrolyte solvent, but acetonitrile (ACN), acetone (DMK), and toluene (Tol) could also be used; lithium iron phosphate was used as the positive electrode material, but lithium cobalt oxide, lithium manganese oxide, and nickel-cobalt-manganese ternary materials could also be used; lithium metal was used as the negative electrode material. ISO and LiTFSI were dissolved in THF at a Li:EO molar ratio of 4.3:1, and polymer electrolyte films were prepared using solvent casting and template methods. In the solution casting method, a small amount (~1 ml) of THF solution was poured into a pre-prepared pen-tube-shaped mold made of Teflon; in the template method, the Teflon mold was used to restrict the flow of the solution during solvent evaporation, ensuring a spherical electrolyte film after solvent evaporation. Subsequently, the sample was placed in a vacuum oven at 120°C and evacuated for 48 hours to remove most of the solvent. Then, the sample was transferred to a glove box under a nitrogen atmosphere and allowed to stand for 1–2 weeks until the solvent completely evaporated, resulting in an ISO / LiTFSI all-solid-state polymer electrolyte membrane. A 1 g / mL LiTFSI THF solution was prepared as the electrolyte and placed in a narrow-mouthed bottle with a sealed stopper. In the glove box, the ISO / LiTFSI all-solid-state polymer electrolyte membrane was immersed in the LiTFSI solution for approximately 3 minutes. The immersed electrolyte membrane was carefully removed from the narrow-mouthed bottle, and the solvent on the sample surface was carefully wiped off with lens paper. The sample was then allowed to stand in a glove box (nitrogen atmosphere) for 1–10 hours to ensure that free THF solvent molecules were removed. The room-temperature ionic conductivity of the obtained electrolyte membrane was measured using electrochemical impedance spectroscopy. The room-temperature ionic conductivity of the obtained sample was 1.4 × 10⁻⁶. -3 S / cm, significantly higher than ~1×10⁻⁶ for ISO / LiTFSI all-solid-state polymer electrolyte films without interface modification. -5S / cm. The electrolyte membrane was assembled with the previously prepared positive and negative electrodes to form a CR2032 battery for battery performance testing. At room temperature, the constant current charge-discharge capacity at 0.1C reached 158 mAh / g. After 100 charge-discharge cycles, the battery showed no significant capacity decay, indicating good capacity retention.

[0026] Example 3 Lithium bis(trifluoromethanesulfonyl)amino (LiTFSI) and polyisoprene-g-polymethyl methacrylate (PMMA-g-NR, MG30) graft copolymer were used as the electrolyte salt and polymer matrix material, respectively; lithium iron phosphate was used as the positive electrode material, and lithium cobalt oxide, lithium manganese oxide, or nickel-cobalt-manganese ternary materials could also be used as the positive electrode; lithium metal was used as the negative electrode material. MG30 and LiTFSI were mixed at a Li to MMA molar ratio of 2:1 using melt mixing technology (refer to patent numbers: ZL202011643287.1 and ZL202010041632.8) to prepare a solvent-free solid electrolyte film. A 1 g / mL LiTFSI THF solution was prepared as the electrolyte and placed in a narrow-mouthed bottle with a sealed stopper. In a glove box, the MG30 / LiTFSI all-solid polymer electrolyte film was immersed in the above LiTFSI solution for ~5 minutes. Carefully remove the soaked electrolyte membrane from the narrow-mouth bottle and gently wipe the solvent off the sample surface with lens paper. Then, place the sample in a glove box (nitrogen atmosphere) for 1–10 hours to ensure that free THF solvent molecules are removed. Measure the room-temperature ionic conductivity of the obtained electrolyte membrane using electrochemical impedance spectroscopy. The room-temperature ionic conductivity of the obtained sample is 4.6 × 10⁻⁶. -4 S / cm, significantly higher than the ~1×10⁻⁶ of the MG30 / LiTFSI all-solid-state polymer electrolyte film without interface modification. -6 S / cm. The electrolyte membrane was assembled with the previously prepared positive and negative electrodes to form a CR2032 battery for battery performance testing. At room temperature, the constant current charge / discharge capacities at different rates (0.1C, 0.5C, 1C, 2C, 3C, 5C) reached 161.5 mAh / g, 140 mAh / g, 122 mAh / g, 102 mAh / g, 88 mAh / g, and 62.5 mAh / g, respectively. Furthermore, the battery capacity retention rates after 1000 and 2000 cycles at 1C were 75% and 50%, respectively, at room temperature. This indicates that the battery has good fast-charging potential and excellent charge / discharge capacity retention.

[0027] Example 4 Zinc trifluoromethanesulfonate (Zn(OTF)2) and polyisoprene-g-polymethyl methacrylate (PMMA-g-NR, MG30) graft copolymer were used as the electrolyte salt and polymer matrix material, respectively; vanadium pentoxide was used as the positive electrode material, although manganese dioxide could also be used; zinc metal was used as the negative electrode material. A solvent-free solid electrolyte membrane was prepared by melt mixing (refer to patent numbers: ZL202011643287.1 and ZL202010041632.8) with MG30 and Zn(OTF)2 in a Zn to MMA molar ratio of 2:1. A propylene carbonate (PC) solution with a Zn(OTF)2 concentration of 1 g / mL was prepared as the electrolyte and placed in a narrow-mouthed bottle with a sealed stopper. In a glove box, the MG30 / Zn(OTF)2 all-solid polymer electrolyte membrane was immersed in the Zn(OTF)2 solution for ~3 minutes. Carefully remove the soaked electrolyte membrane from the narrow-mouth bottle and gently wipe the solvent off the sample surface with lens paper. Then, place the sample in a glove box (nitrogen atmosphere) for 1–10 hours to ensure that free PC solvent molecules are removed. Measure the room-temperature ionic conductivity of the obtained electrolyte membrane using electrochemical impedance spectroscopy. The room-temperature ionic conductivity of the obtained sample is 1.2 × 10⁻⁶. -4 S / cm, significantly higher than the ~1×10⁻⁶ of the MG30 / Zn(OTF)₂ all-solid-state polymer electrolyte film without interface modification. -7 S / cm. The electrolyte membrane was assembled with the previously prepared positive and negative electrodes to form a CR2025 battery for battery performance testing. At room temperature, the constant current charge-discharge capacity at 0.1C reached 30 mAh / g. After 20 charge-discharge cycles, the capacity did not decrease, indicating good cycle performance.

[0028] To verify the effect of thin film surface wetting modification on the electrochemical performance of solid electrolytes, the applicant conducted the following study: In the preparation process of the all-solid-state electrolyte film in Example 3, inorganic fillers (Al2O3 and LATP) with a lithium salt mass fraction of 10% were added to prepare MG30 / LiTFSI / Al2O3 and MG30 / LiTFSI / LATP polymer-inorganic composite solid-state electrolytes, respectively. The same surface wetting modification process as in Example 3 was used. Room temperature ionic conductivity was measured using electrochemical impedance spectroscopy. The room temperature ionic conductivity of the obtained MG30 / LiTFSI / Al2O3 and MG30 / LiTFSI / LATP samples were ~10⁻⁶. - 9 S / cm, ~10 -6 S / cm. This value is significantly lower than the room temperature ionic conductivity of 4.6 × 10⁻⁶ for the MG30 / LiTFSI sample without inorganic filler. -4S / cm. Furthermore, the solid-state lithium metal battery assembled based on MG30 / LiTFSI / Al2O3 failed to operate, while the initial capacity of the solid-state lithium metal battery assembled on MG30 / LiTFSI / LATP was only 15 mAh / g (0.1 C), far lower than the 161.5 mAh / g of the surface-wetting modified MG30 / LiTFSI solid-state lithium metal battery. This indicates that the addition of inorganic fillers weakens or destroys the surface wetting modification effect of the solid electrolyte membrane, thus leading to poor electrochemical performance.

[0029] For any points not covered above, existing technologies shall apply.

[0030] Although specific embodiments of the present invention have been described in detail by way of examples, those skilled in the art should understand that the above examples are for illustrative purposes only and are not intended to limit the scope of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them, without departing from the direction of the invention or exceeding the scope defined by the appended claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc., made to the above embodiments based on the technical essence of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for modifying the interface of an all-solid-state polymer electrolyte, characterized in that, Based on the types of polymers and electrolyte salts in the all-solid polymer electrolyte membrane, a good solvent that is both a polymer and an electrolyte salt is selected. The electrolyte salt is used to prepare an electrolyte solution with the selected solvent. The all-solid polymer electrolyte membrane is immersed in the electrolyte solution, and the immersion time is controlled. The all-solid polymer electrolyte membrane is then removed from the electrolyte solution, and the free solvent molecules on the surface of the all-solid polymer electrolyte membrane are removed. An interface-modified all-solid polymer electrolyte membrane is obtained through the complexation between the solvent molecules and the polymer and electrolyte salt. The modified all-solid polymer electrolyte membrane does not contain free solvent molecules. The specific steps for removing free solvent molecules from the surface of the all-solid polymer electrolyte membrane include: carefully removing the soaked electrolyte membrane from the narrow-mouth bottle, carefully wiping the solvent off the sample surface with lens paper, and then letting the sample stand in a nitrogen atmosphere in a glove box for 1 to 10 hours to ensure that the free solvent molecules are removed; The soaking time is 30~300s.

2. The method for modifying the interface of an all-solid-state polymer electrolyte as described in claim 1, characterized in that, The polymers include any one of polyethylene oxide, polyisoprene-b-polystyrene-b-polyoxyethylene block copolymer, and polyisoprene-g-polymethyl methacrylate graft copolymer.

3. The method for modifying the interface of an all-solid-state polymer electrolyte as described in claim 2, characterized in that, The electrolyte salt is any one or more of lithium salt, sodium salt, potassium salt, and zinc salt.

4. The method for modifying the interface of an all-solid-state polymer electrolyte as described in claim 3, characterized in that, The solvents include one or more of tetrahydrofuran, 1,3-dioxapentane, diethyl carbonate, ethylene carbonate, propylene carbonate, acetonitrile, toluene, and acetone.

5. A surface-modified all-solid-state polymer electrolyte membrane, characterized in that, It is prepared by the interface modification method as described in any one of claims 1-4.

6. The application of the surface-modified all-solid polymer electrolyte membrane as described in claim 5 in the preparation of secondary ion batteries.

7. The application as described in claim 6, characterized in that, The secondary ion battery includes any one of lithium secondary batteries, zinc secondary batteries, potassium secondary batteries, and sodium secondary batteries.

8. A secondary ion battery comprising a positive electrode, a negative electrode, and a separator disposed between the positive and negative electrodes, characterized in that, The diaphragm comprises the surface-modified all-solid polymer electrolyte membrane as described in claim 5.

Citation Information

Patent Citations

  • A method for batch preparation of all-solid polymer electrolyte membranes using a two-roll mill

    CN111224152B

  • A polymer electrolyte thin film, its preparation method and its application

    CN112778677B

  • Modified polymer electrolyte, preparing method of modified polymer electrolyte and application of modified polymer electrolyte to lithium battery

    CN103985900A